SYSTEMATIC LITERATURE REVIEW: MODUL AJAR DIGITAL BERBASIS OPEN-ENDED PADA PEMBELAJARAN MATEMATIKA - Pratiwi, Nisa Umi; Luthfiana, Maria; Yanto, Yufitri (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
The aim of this research is to produce a digital mathematics learning module based on an open-ended approach to mathematics learning. This type of research is development research with an Open - Ended model. The steps include presenting the problem, designing the lesson, paying attention to and recording student responses, guiding and directing students and making conclusions. The subjects in this research were class VII junior high school students. The results of this research show that digital learning modules based on an open-ended approach can improve students' creative mathematical thinking, this is based on the test results obtained.